Successful Diagnosis and Management in 28-week Preterm Infant with Gastrointestinal Perforation - A Case Report - Fadhilah Hana; Dito Desdwianto; Cherie Nurul Farid Lubis (The Indonesian Society of Pediatric Gastroenterology, Hepatology, and Nutrition, 2026)
Background: Gastrointestinal perforation (GIP) appears as an important reason for mortality during neonatal period, with reported high prevalence ranging from 15 - 70%. The perforation may be related to a variety of caused such as necrotizing enterocolitis (NEC), iatrogenic caused, obstruction of intestinal or spontaneous. The current standard treatment is surgery. Despite surgical intervention, the mortality rate remains significantly high about 49% in very low birth weight and low birth weight infants. Objective: The aim of this study was to report our hospital’s intensive care and surgical experience in managing gastrointestinal perforation among very preterm and very low birth weight infant. Case: A female baby, 980 gr of birth weight, was delivered by caesarean section at 28-weeks of gestation due to maternal severe pre-eclampsia and premature ruptured of membrane (>12 hours). Antenatal corticosteroid was completed before birth. The baby had respiratory distress syndrome and required immediate to NICU admission. Early oral care with breast milk had been given < 24 hours life. Unfortunately, at third days of age, she had an abdominal distention and diagnosed with acute abdomen. Free air in the abdomen seen on an X-ray indicated a pneumoperitoneum. An emergency surgery was performed immediately with pediatric surgeon, rupture of gaster was found. Primary repair gastric and omental patch were performed. She passed the critical period after surgery and improved, she was extubated on the seventh day after the operation. A trial feed was well tolerated. The baby was discharged and doing well on follow-up.